2008
DOI: 10.1021/jm701490g
|View full text |Cite
|
Sign up to set email alerts
|

β-Homo-amino Acid Scan of Angiotensin IV

Abstract: Angiotensin IV, a metabolite of angiotensin II, inhibits the enzyme insulin regulated aminopeptidase or IRAP and also, although with lower potency, aminopeptidase-N (AP-N). When both beta (2)-homo amino acid- and beta (3)-homo amino acid substitutions were used, allowed the identification of H-( R)beta (2)hVal-Tyr-Ile-His-Pro-beta (3)hPhe-OH as a potent and stable Ang IV analog with high selectivity for IRAP versus AP-N and the AT1 receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 38 publications
7
84
0
Order By: Relevance
“…Efforts were taken to develop AngIVderived IRAP inhibitors with improved selectivity versus AP-N and the AT 1 receptor, as well as resistance to proteolytic degradation. Lukaszuk et al, 2008) reported that the AngIV analog AL-11 (pK i 7.25 for IRAP enzyme activity) in which the b-homo amino acid b obtain AL-40 with a pK i is 8.07 for IRAP (Lukaszuk et al, 2009). Substitution of the latter Gly 5 by norvaline led to an analog (IVDE77) with further increased affinity (pK i is 8.77 for IRAP) Nikolaou et al, 2013).…”
Section: Pharmacology Of Angiv Analogsmentioning
confidence: 99%
“…Efforts were taken to develop AngIVderived IRAP inhibitors with improved selectivity versus AP-N and the AT 1 receptor, as well as resistance to proteolytic degradation. Lukaszuk et al, 2008) reported that the AngIV analog AL-11 (pK i 7.25 for IRAP enzyme activity) in which the b-homo amino acid b obtain AL-40 with a pK i is 8.07 for IRAP (Lukaszuk et al, 2009). Substitution of the latter Gly 5 by norvaline led to an analog (IVDE77) with further increased affinity (pK i is 8.77 for IRAP) Nikolaou et al, 2013).…”
Section: Pharmacology Of Angiv Analogsmentioning
confidence: 99%
“…Both potent and specific drug-like IRAP inhibitors (Borhade et al, 2014;Mountford et al, 2014), some with proven effects in vivo (Albiston et al, , 2011, and inhibitors with more peptidic character (Kobori et al, , 1998Wolfe, 2002;Axen et al, 2006;Axen et al, 2007;Andersson et al, 2008;Lukaszuk et al, 2008Lukaszuk et al, , 2009Hallberg, 2009) have been disclosed by us and others. We use an approach to discover efficient Ang IV peptidomimetics that relies on stepwise alterations of Ang IV by applying various cyclization procedures to restrict conformational flexibility and to allow determination of the bioactive conformation of Ang IV when it binds to IRAP (Axen et al, 2006(Axen et al, , 2007.…”
Section: Introductionmentioning
confidence: 93%
“…In view of the potential impact of IRAP binding on the NF-κB pathway, 30,31 we investigated the modulatory activity of Ang IV and the stable Ang IV-analogue AL-11 33 on the expression of NF-κB regulated genes (inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), tumor-necrosis factor α (TNFα), intercellular adhesion molecule 1 (ICAM-1)) in macrophages by quantitative real-time PCR (Table 1). None of these genes were induced by Ang IV or AL-11, suggesting that IRAP binding does not directly stimulate NF-κB signaling in macrophages ( Figure 11).…”
Section: Irap Ligands Do Not Modulate Nf-κb Regulated Gene Expressionmentioning
confidence: 99%